Studies on Effective Utilization of WTP Sludge in Brick Manufacturing and its Economic Analysis: Exploring the Potential of WTP Sludge in Improving Brick Manufacturing Process (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is second largest producer of bricks. accounting for over l0°o of the global production. As bricks are economical. durable and easy to handle these are widely used in India. The demand for bricks has been increasing year by year with the increased building construction activities. 140 billion bricks were produced in 2001 and 250 billion bricks in 2012. The production of bricks is estimated to be growing at a rate of 4 per year. India is the largest producer of ﬁred clay bricks with more than hundred thousand brick kilns in operation. The brick sector is growing as the demand for bricks is increasing in the towns and villages due to the fast economic growth, urbanization and prosperity. India’s brick sector is characterized by traditional ﬁring technologies, high dependency on human and animal labour and low mechanization rate, Brick sector in India is of small-scale with limited financial, technical and managerial capacity. Brick industry in India is widely spread all around but situated in rural and periphery of urban areas. Quality of brick changes from place to place due to changes in raw material and manufacturing process of brick. The brick manufacturing process is conventional and brick industry is unorganized. Different parts of country produce bricks with different engineering properties. Bricks from northern India region, which lies in the lndo-Gangetic plains have good engineering properties as compared to bricks from others parts of India. In this research the water treatment sludge is utilized for manufacturing the clay bricks